Mental Health Problems Due to Social Isolation During the COVID-19 Pandemic in a Mexican Population - Genis-Mendoza, Alma Delia; Martínez-Magaña, José Jaime; López-Narváez, María Lilia; González-Castro, Thelma Beatriz; Juárez-Rojop, Isela Esther; Nicolini, Humberto; Tovilla-Zárate, Carlos Alfonso; Castillo-Avila, Rosa Giannina (Frontiers in Public Health, 2021)
Introduction: Social isolation due to the COVID19 pandemic has been identified as a risk factor of several mental disorders. Therefore, the present work aimed to evaluate the effect of social isolation experienced during the COVID19 pandemic on the mental health of a Mexican population. Material and methods: A cross-sectional online survey was conducted in individuals of 18 years of age and over. The questioner was structured to identify onset or worsening of psychiatric symptoms due to social isolation during the COVID19 pandemic. The survey included changes in eating habits, changes in personal hygiene habits, the starting the use or increased the use of psychoactive substances, symptoms of depression or post-traumatic stress. Results: A total of 1011 individuals were included in this study. The majority were women (68.84%). Changes in eating habits were reported in 38.51% of the participants, 67.80% reported having their physical self-perception distorted or having started a low-calorie diet. Regarding symptoms of depression, 46.10% participants indicated to have at least one depressive symptom, and 4.46% reported suicidal ideation during social isolation. Interestingly, 6.09% of individuals reported that they used to have depressive symptoms prior the COVID-19 pandemic and those symptoms decreased during the social isolation. Additionally, 2.27% of individuals presented symptoms of post-traumatic stress due to the possibility of getting COVID19. Conclusions: In this work we identified how social isolation has impacted the mental health of the Mexican population. We observed that practically all the majority of characteristics evaluated, changed during isolation, such as personal hygiene and eating habits, as well as depression, post-traumatic stress and substance use. Depression and suicidal ideation increased in the general population; while in individuals who had symptoms of depression before isolation, these symptoms decreased during social isolation.